IQ Domain-Containing GTPase-Activating Protein 1 Regulates Cytoskeletal Reorganization and Facilitates NKG2D-Mediated Mechanistic Target of Rapamycin Complex 1 Activation and Cytokine Gene Translation in Natural Killer Cells - Abel, Alex M.; Tiwari, Aradhana A.; Gerbec, Zachary J.; Siebert, Jason R.; Yang, Chao; Schloemer, Nathan J.; Dixon, Kate J.; Thakar, Monica S.; Malarkannan, Subramaniam (Frontiers in Immunology, 2018)
Natural killer (NK) cells are innate lymphocytes that play essential roles in mediating anti-tumor immunity. NK cells respond to a variety of inflammatory stimuli including cytokines and stress-induced cellular ligands which activate germline-encoded activation receptors (NKRs), such as NKG2D. The signaling molecules activated downstream of NKRs are well defined; however, the mechanisms that regulate these pathways are not fully understood. IQ domain-containing GTPase-activating protein 1 (IQGAP1) is a ubiquitously expressed scaffold protein. It regulates diverse cellular signaling programs in a variety of physiological contexts, including immune cell activation and function. Therefore, we sought to investigate the role of IQGAP1 in NK cells. Development and maturation of NK cells from mice lacking IQGAP1 (Iqgap1-/-) were largely intact; however, the absolute number of splenic NK cells was significantly reduced. Phenotypic and functional characterization revealed a significant reduction in the egression of NK cells from the bone marrow of Iqagp1-/- mice altering their peripheral homeostasis. Lack of IQGAP1 resulted in impaired NK cell motility and their ability to mediate anti-tumor immunity in vivo was also impaired. Activation of Iqgap1-/- NK cells via NKRs, including NKG2D, resulted in significantly reduced levels of inflammatory cytokines compared to WT. This reduction in Iqgap1-/- NK cells is neither due to an impaired membrane proximal signaling nor a defect in gene transcription. , The levels of Ifng transcripts were comparable, suggesting that IQGAP1-dependent regulation of cytokine production is regulated by a post-transcriptional mechanism. To this end, Iqgap1-/- NK cells failed to fully induce S6 phosphorylation and showed significantly reduced protein translation following NKG2D-mediated activation, revealing a previously undefined regulatory function of IQGAP1 via the mechanistic target of rapamycin complex 1 (mTORC1). Together, these results implicate IQGAP1 as an essential scaffold for NK cell homeostasis and function and provide novel mechanistic insights to the post-transcriptional regulation of inflammatory cytokine production.